SELECTED ASPECTS OF QUALITY DEVELOPMENT IN HOTEL INDUSTRY ON THE EXAMPLE OF THE POLISH PRESTIGE HOTELS & RESORTS GROUP - Maria Bigos; Bogusław Sawicki (Acta Scientiarum Polonorum. Oeconomia, 2010)
The study presents the process of achieving a competition advantage by developing a hotel product, on the basis of combining quality with innovation and new technology. The role of organisational culture, standardisation and technology in the development of hospitality services is discussed here. The study also presents a quality programme bringing together several dozen Polish hotels, which functions under the name PPH&R. The convergence of goals between the development of quality, brand and public relations is pointed out. What is also stressed is the role of cultural heritage in the implementation of the PPH&R programme, which brings advantages to both providers of hospitality services and guests using the services.